91O A multi-center phase IIa trial to assess the safety and efficacy of BL-8040 (a CXCR4 inhibitor) in combination with pembrolizumab and chemotherapy in patients with metastatic pancreatic adenocarcinoma (PDAC). (15th December 2019) - Hidalgo, M; Semenisty, V; Bockorny, B; Borazanci, E; von Hoff, D D; Feliu, J; Sarvise, M Ponz; Abad, D Gutierrez; Peled, A; Bohana-Kashtan, O; Gozlan, Y; Sorani, E; et al.
Abstract: Background: Current treatment options for PDAC are limited. While PD-1/PD-L1 antagonists have shown promising results in other cancer types, this approach has been ineffective in PDAC. In Cohort 1 of the COMBAT study, the dual combination of BL-8040 (a CXCR4 inhibitor) and Pembrolizumab was safe and showed a promising 7.5 mo OS in 2L patients. BL-8040 modified the TME by promoting infiltration of effector T cells and decreasing immune suppressor cells. Based on these encouraging results, as well as preclinical data supporting the combination of BL-8040, Pembrolizumab and chemotherapy, the study was expanded to include a combination arm (Cohort 2) composed of BL-8040, Pembrolizumab and chemotherapy (Onivyde/5-FU/LV). Here we report the preliminary safety and efficacy of BL-8040 in this expansion cohort. Methods: Phase IIa study, Cohort 2, treatment regimen consists of 5 days BL-8040 priming monotherapy followed by combination treatment of Onivyde/5-FU/LV every 2 weeks, Pembrolizumab every 3 weeks and BL-8040 twice a week. Eligibility criteria includes metastatic PDAC subjects with measurable disease by RECIST1.1 that have progressed following first-line treatment with gemcitabine-based chemotherapy. Results: This is a snapshot of Cohort 2 of the COMBAT study. As of September 2019, 22 patients have been enrolled, of which 15 are evaluable (i.e. received at least 1 dose of combination and have post-baseline CT). Median age 68, ECOG≤1 and 60% males. 15 SAEs were reported by 10 patients. 2 subjects were discontinued due to SAEs. Best Response by RECISTv1.1 for the evaluable population showed 4 partial response (PR) and 8 stable disease (SD) patients, a total of 12 subjects with disease control (DC) out of 15. Median PFS and OS were not reached. Notably all patients with PR and SD had an initial increase in CA 19-9 followed by a decrease. Tumor shrinkage began during the transient increase of CA 19-9. Conclusion: Preliminary data from the ongoing COMBAT study Cohort 2 with the triple combination of BL-8040, Pembrolizumab and chemo, show promising ORR (4/15) and DC (12/15) results. Median PFS and OS have not yet been reached. Clinical trial identification: NCT02826486. Legal entity responsible for the study: The authors. Funding: Biolinerx. Disclosure: M. Hidalgo: Full / Part-time employment: Beth Israel Deaconess Medical Center; Full / Part-time employment: Harvard Medical School; Full / Part-time employment: Weill Cornell Medical College. V. Semenisty: Full / Part-time employment: Rambam Health Care Campus. B. Bockorny: Full / Part-time employment: Beth Israel Deaconess Medical Center; Research grant / Funding (institution): NanoView Biosciences. E. Borazanci: Full / Part-time employment: Honor-Health/TGen. D.D. von Hoff: Full / Part-time employment: Honor-Health/TGen. J. Feliu: Advisory / Consultancy, Travel / Accommodation / Expenses: Amgen; Advisory / Consultancy: Ipsen; Advisory / Consultancy: Roche; Advisory / Consultancy: Novartis; Advisory / Consultancy: Eisai; Advisory / Consultancy: Merck; Travel / Accommodation / Expenses: Seriver. M. Ponz Sarvise: Full / Part-time employment: Clinica Universidad de Navarra. D. Gutierrez Abad: Full / Part-time employment: Grupo Oncologia Fuenlabrada. A. Peled: Full / Part-time employment: Goldyne Savad Institute of Gene Therapy; Leadership role: Biokine Therapeutics Ltd. O. Bohana-Kashtan: Full / Part-time employment: Biolinerx. Y. Gozlan: Full / Part-time employment: Biolinerx. E. Sorani: Honoraria (self), Leadership role, Shareholder / Stockholder / Stock options, Full / Part-time employment: Biolinerx. M. Chaney: Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc. S. Kadosh: Full / Part-time employment: StatExcellence. A.V. Vainstein: Honoraria (self), Leadership role, Shareholder / Stockholder / Stock options, Full / Part-time employment: Biolinerx. T. Macarulla: Full / Part-time employment: Vall d´Hebron University Hospital.